Device thrombosis in the Heartware LVAD treatment decision and role of log files. (25th November 2020) - Demir, E; Nalbantgil, S.N; Ozturk, P.O; Candemir, A.C; Kahraman, U.K; Engin, C.E; Yagdi, T.Y; Saeed, O.S; Jorde, U.J; Ozbaran, M.O
Abstract: Background: Device thrombosis is a significant problem during durable LVAD support, and device-specific diagnosis and treatment algorithms are necessary to optimize outcomes. The HVAD LVAD has a unique and well-developed logfile capability, yet clinical data on it's use are lacking. Methods and results: We reviewed overall outcomes of 322 consecutive patients implanted at our University Medical Center with the HVAD LVAS with a particular emphasis on device thrombosis events. Thirty days, one year, and two years survival was 85.4%, 65.0%, and 53.1%, respectively. One hundred eighty-one device thrombosis events occurred in 76 patients. Based on logfile patterns, events were categorized as gradual build-up or sudden build-up or acute occlusion/ingestion (Jorde U JACC-HF 2015). The first thrombosis event was a gradual build-up in 32, sudden build up in 5, and acute occlusion in 11 pts. An additional 46 gradual build-up, two sudden build-up, nine acute occlusion events occurred as recurrent events. 2-year survival without CVA was 72.8% in patients with gradual onset device thrombosis 72 pts received TPA. TPA was given, after discontinuing anticoagulation, and taking the INR level is under 2.0 and keeping invasively measured mean arterial blood pressure between 65–80 mmHg low dose tenecteplase (1000 units) was then given, and if clinical and logfile improvement did not occur repeated every six hours up to a total fo 4 doses (4000 units) over 24 hours. Successful therapy was defined as clinical resolution of pump thrombosis without recurrence in 30 days, LDH improvement and power consumption returned to normal, and occurred in 74.4% gradual onset, 71.4% sudden onset, and 56.3% acute occlusion. TPA was complicated by severe hemorrhage or death in 6.4% of patienst with a gradual build-up pattern, 14.3% with sudden build-up, and in 33.3% with acute occlusion. Conclusion: Device thrombosis frequently occurs in HVAD patients, and response to therapy can be predicted by logfile analysis. TPA is an excellent option for gradual onset device thrombosis but should be avoided in the setting of acute occlusions, where early device exchange may be a better first-line strategy. Refinement of logfile analysis including earlier thrombus detection and incorporation of these techniques into clinical practice may significantly improve outcomes with the HVAD LVAD. Funding Acknowledgement: Type of funding source: None